A província autofágica de Dalton Trevisan: o real, o resto e o vazio no ventre do Minotauro - Locatelli, Renan Gonçalves (2026)
This thesis investigates the category of the province in the work of Dalton Trevisan, proposing to understand it beyond its geographical or sociocultural meaning, as a critical figure of a negative ontology marked by the real, the remainder and the void. The study addresses the problem of understanding how thematic recurrence, formal repetition and the insistence on figures of violence, enclosure, and negativity, often interpreted as aesthetic impoverishment, actually constitute a rigorous literary project traversed by the traumatic experience of the real. The central hypothesis argues that, in Trevisan’s writing, the province operates as an autophagic space: a place that devours itself, reiterating the impossibility of stabilizing meaning and identity, while simultaneously exposing the limits of symbolization. The research aims to analyze how the province is articulated in the author’s work as a return of the real and as a category of remainder. The corpus privileges Antologia pessoal (2023), understood as a point of condensation and balance within the oeuvre, without excluding dialogue with other books by the author, especially those that thematize Curitiba and its recurring figures. The theoretical framework articulates contributions from literary criticism and psychoanalysis, with emphasis on the studies of Waldman (2014), Foster (2017), Rolnik (2021), Kehl (2007 e 2017) and Piglia (2004a e 2004b). These references allow the province to be understood as a figure of the impossible, linked to traumatic experience and the failure of representation. In the final considerations, it is concluded that the autophagic province does not constitute a space of identity or belonging, but rather a regime of negativity that sustains the aesthetic power of Dalton Trevisan’s work. Repetition emerges as the insistence of the real and as the foundation of a writing that transforms void, silence and remainder into critical operators of contemporary literature